Women empowerment through microfinance: A case study of women in self help group of Uthangarai Taluk in Krishnagiri district Tamilnadu - Palanichamy, *A.P. (International Multidisciplinary Research Journal, 2011)
The Indian women from an active section of the soy and the involve in all sort of functions and per forming all kinds of duties similar to man. The women as responsible citizens of the country achieving social and economic status in the all stages of economic and social activities involved of win has given added SHGs in many parts of the country; house achieved success in bringing the woman to be rain stream of decision making. Against the background of hate patriarchates system of society the women need special attention to ensure their development and participation in the decision making process at home in to community and governance. For women to become a success fuel entrepreneurs she needs aces to capital technical and managerial know how and market. The ensure to empower rural women lies in catalyzing opportunities for them to earn higher income in order to in prove their standard of living the objective could be accomplished by establishing enterprises that are based on the locally available resources and profitable indigenous knowledge.